The Inclusion of an Interdisciplinary Expert Advisory Group in Doctoral Research on Chaplaincy: Insights from Two Doctoral Researchers - Saliba, Serena Margaret (Journal of pastoral care & counseling, 2025)
This paper advocates for including an interdisciplinary expert advisory group in doctoral research, particularly for interdisciplinary or transdisciplinary research. Five benefits were identified: uncovering blind spots, fostering diverse perspectives on the topic, providing opportunities for researchers to explore related areas, enabling collaboration amongst experts, and offering structure to the doctoral project. This approach enhances the quality and breadth of doctoral research by integrating expertise from multiple disciplines.